LATE NEOPROTEROZOIC RARE-METAL LEUCOGRANITE FROM THE KHARIUSIKHA MASSIF OF YENISEI RIGDE: GENESIS AND RELATIONSHIP TO MAGMATISM OF A LARGE IGNEOUS PROVINCE - A. D. Nozhkin; O. M. Turkina (Геодинамика и тектонофизика)
The paper deals with the petrogeochemical composition and U-Pb (SHRIMP-II) age (753±6 Ma) of subalkaline leucogranites and syenites from the Khariusikha massif of the Yenisei Ridge, which contain rare-metal mineralization. High trace-element concentrations (%) – Nb (0.5–0.7), Ta (0.12–0.16), REE (0.08–0.24), Y (0.06–0.10), Zr (2.3–2.6), Hf (0.10–0.12), U (0.05–0.10) and Th (0.08–0.10) – are confined to albitized granites. Synthesis information on age and composition of rhyolites of the bimodal volcanic associations of the Upper Vorogovka and Glushikha troughs and subsynchronous granitoids of the Trans-Angarian Yenisei Ridge indicates A-type granitoids. Their formation is limited to 750–720 Ma interval and is temporally correlated with the formation of a Late Neoproterozoic large igneous province whose ultrabasite-basite magmatism is localized along the present-day southern flank of the Siberian Platform. The considered volcanic and intrusive rocks are characterized by wide-range high field strength element concentrations and εNd(t) values ranging from –9.2 to +0.7. Crustal sources are dominant for most of the felsic magmatic rocks. A probable contribution of the mantle source to felsic magmas generation is evidenced by more radiogenic Nd isotope composition and enrichment of the Khariusikha massif granites and syenites in high field strength elements, as well as by the similarity of the Upper Vorogovka trough basalts with OIB.